2014
DOI: 10.1080/13102818.2014.909083
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of radiofrequency turbinoplasty in nasal obstruction

Abstract: The aim of this retrospective study is to investigate long term (two years) effect of radiofrequency tissue volume reduction (RFVTR) on nasal obstruction associated with inferior turbinate hypertrophy, which is not respond to medical treatment. This retrospective study carried out on 98 patients with nasal obstruction treated by RFVTR (56 males, 42 females, from 17 to 70 years of age). Visual analogue scales (VAS) and nasal endoscopic view score (NES) were used for nasal obstruction to evaluate the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
(18 reference statements)
0
22
0
Order By: Relevance
“…14 Akdag et al, investigating the long-term effects of radiofrequency on reduction of volume, reported a maximum decrease in the first 3 months, in which the efficacy continued for 20 months. 15 We believe that, given the aim of surgery in a patient with nasal obstruction symptoms is to overcome the obstruction, compensatory lower conchal hypertrophy must be treated simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…14 Akdag et al, investigating the long-term effects of radiofrequency on reduction of volume, reported a maximum decrease in the first 3 months, in which the efficacy continued for 20 months. 15 We believe that, given the aim of surgery in a patient with nasal obstruction symptoms is to overcome the obstruction, compensatory lower conchal hypertrophy must be treated simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of medical treatment will route to various surgical techniques like partial or total turbinectomy, turbinoplasty, sub mucosal electrocautery, radiofrequency ablation, laser assisted resection / ablation and cryosurgeryetc. (1,2,3) Radiofrequency ablation and microdebrider assisted turbinoplasty are functional procedures which conserves mucosal tissue. Goal of inferior turbinate surgery should aims to maximize volumetric reduction of turbinate with improvement in nasal obstruction and maintain nasal function with minimal complications.…”
Section: Introductionmentioning
confidence: 99%
“…Goal of inferior turbinate surgery should aims to maximize volumetric reduction of turbinate with improvement in nasal obstruction and maintain nasal function with minimal complications. (1) Radiofrequency is a method which uses high frequency radio waves that heat the cells of turbinate and consequently causes coagulation necrosis. When thin needle terminals of bipolar probe are inserted into the sub-mucosal tissue which reduces vascular nervous tissue and consequently scar retracts resulting in reduction of volume of turbinate.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The RF that ranges from 300 to 3,000 kHz has been defined as a medium frequency. 13 The target site is stably formed with tissue-reduced volume approximately 3 weeks postoperatively. 13 The studies on the use of RF in cases of rhinitis medicamentosa are very little.…”
Section: Introductionmentioning
confidence: 99%
“…13 The target site is stably formed with tissue-reduced volume approximately 3 weeks postoperatively. 13 The studies on the use of RF in cases of rhinitis medicamentosa are very little. Evidence was available only indirectly, in studies of inferior turbinate hypertrophy.…”
Section: Introductionmentioning
confidence: 99%